Performance Evaluation of Single-Phase Grid-Connected Photovoltaic Inverter Using LC and LCL Filter Based on the Reduction of THD - Repalle Rohit; Gudipati Kishor (International Journal of Integrated Engineering, 2024)
Solar photovoltaic (PV) energy and its applications continue to grow in popularity as a means of enhancing society’s sustainable development. There are a lot of issues to consider when PV systems are linked to the grid. One of the challenges, particularly only with large-scale use of PV systems, is harmonics in PV systems. This research investigates the use of well-known filters to reduce harmonics in PV systems. Filtering is required to decrease the harmonics due to the non-sinusoidal nature of PWM voltages at the converter output. To join the converter to the grid and decrease harmonics, a simple LC filter has traditionally been utilized. The use of LCL filters, on the other hand, has been proposed. The purpose of this research is to look at the impact of T-filters or LCL Filters on the overall working of a photovoltaic system that is connected to a grid. The perturb & observe algorithm is used for MPPT operation and The proportional-integral controller (PI) is used as the current controller in the closed-loop grid-connected PV system for the generation of pulses. The single-Phase Grid-Connected photovoltaic System for both LC & LCL Filters is implemented in this paper using MATLAB/Simulink. Total Harmonic Distortion is utilized as the performance metric in this comparison. The value of %THD for the proposed system i.e.8.06% emphasizes its necessity for implementation in practicality.